Food Bioactives Extraction and Biotechnology Applications - Puri, Munish (Springer International Publishing : Imprint: Springer, 2017)
This book focuses on various types of bioactive compounds, including secondary metabolites, oligosaccharides, polysaccharides, flavonoids, peptides/proteins, carotenoid pigments, quinones, terpenes, and polyunsaturated fatty acids, and presents an overview of their nutraceutical activities. It covers the current status and future potential of food compounds, as well as extraction technologies for biaoctives derived from plant, fungi and marine-derived bioactive agents. Finally, health-promoting effects of plant, fungi and marine-derived bioactive agents are discussed. Chapters come from top researchers in this area from around the globe. The volume caters to the needs of undergraduate and post-graduate students in the area of food biotechnology, food bioprocessing, biotechnology, food engineering, etc., and also contains information pertinent to researchers. .